The effect of adding quicklime on stabilization of expansive soils - Sudjianto, Agus Tugas; Vili, Arnol Da Costa De Jesus; Suraji, Aji; Riman, Riman; Susilo, Sugeng Hadi (Technology audit and production reserves, 2025)
The object of this research is Ampelgading clay (Malang, East Java), known for its high plasticity and low strength, which impact building stability. This study focuses on how varying proportions of quicklime affect soil properties. One of the main issues is clay instability, caused by volume changes due to water fluctuations, which poses a major challenge for infrastructure, particularly in high-rainfall and humid areas. In the study, expansive clay from Ampelgading with quicklime percentages of 0 %, 5 %, 10 %, 15 %, and 20 % was tested. Geotechnical and mechanical tests, including water content, specific gravity, Atterberg limits, compressive strength, and swelling, were conducted. The results show that adding quicklime significantly alters the physical and mechanical properties of the clay, reducing water content from 58.20 % to 35.64 % and specific gravity from 3.362 to 2.118. Volumetric weight initially increases at low quicklime levels but decreases at higher levels. Quicklime alters soil microstructure through a pozzolanic reaction with calcium hydroxide (Ca(OH)₂) and silica/alumina, forming calcium hydrates that enhance cohesion and strength. However, excessive quicklime creates non-uniform aggregates, reducing density and stability. Optimal compressive strength occurs at 15 % quicklime, but at 20 %, stability decreases, plasticity reduces, and swelling accelerates. Furthermore, lower moisture content improves compaction and enhances soil stability. Compared to cement or fly ash, quicklime reacts faster, provides immediate stability, and minimizes long-term swelling and shrinkage. The pozzolanic reaction further strengthens the soil by forming stable calcium hydrate and calcium aluminate compounds.